Model Pendidikan Beyond the Wall dalam Pendidikan Agama Kristen dan Tantangan Kemajemukan Agama di Sekolah - Maelissa, Nova (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2024)
This research intends to analyze the model of education beyond the wall in Christian religious education and the challenges of pluralism that exist in schools. The implementation of Christian religious education in schools is not easy. There are problems of religious pluralism faced by teachers and students in schools. For this reason, a special approach is needed to overcome these problems so that Christian religious education can achieve its goal of accepting pluralism as a gift from God. A qualitative method with a literature study approach was used in this research. The results show that the education model beyond the wall is an ideal model that should be developed into a contextualized pattern of religious teaching in schools. This model not only provides space for static dialogical relationships, but more than that, it invites students with various religious and ethnic backgrounds to work together to build peace and voice justice for the creation of a safe, peaceful and harmonious society.